KAJIAN GOOD GOVERNANCE SINGAPURA DAN INDONESIA: STUDI PEMBERANTASAN KORUPSI [Singapore and Indonesia's Good Governance Review: An Anticorruption Study] - Andreas Sulardi; Anna Erliyana (Law Review, 2021)
Eradication of Corruption in Indonesia in 2015-2019 in a row did not experience significant progress. In contrast to Indonesia, in 2019 Singapore actually occupied the number two position for the Asia Pacific region and number one in the ASEAN region in eradicating corruption. How to compare the eradication of corruption in the two countries? This article will explore the eradication of corruption in Singapore and Indonesia with a Good Governance approach and analysis of data reading from the two countries’ corruption eradication institutions. The results show that there are three key pillars in eradicating corruption in Singapore which consist of political will, independence, and effectiveness of corruption eradication institutions, and the application of good administrative services. The results of the next study explained that the eradication of corruption in the 2015-2019 period in Indonesia was deemed not optimal due to three things: political patronym and the power of investors that hindered the eradication of corruption, the ineffectiveness of taking action against the KPK, and the vision of Jokowi’s leadership that was too focused on the development and economic growth but did not pay attention to it. bureaucratic reform agenda. The benefits of this paper are primarily intended to assist Indonesia in optimizing the eradication of corruption by learning from Singapore. It is hoped that good and corruption-free governance can be implemented in Indonesia.Bahasa Indonesia Abstrak: Pemberantasan Korupsi di Indonesia pada 2015-2019 secara berturut-turut tidak mengalami kemajuan yang berarti. Berbeda dengan Indonesia, pada 2019 Singapura justru menduduki posisi nomor dua untuk wilayah Asia Pasifik dan nomor satu di wilayah ASEAN dalam pemberantasan korupsi. Bagaimana membandingkan pemberantasan korupsi pada kedua negara tersebut? Artikel ini hendak mengupas pemberantasan korupsi Singapura dan Indonesia dengan pendekatan Good Governance dan analisa pembacaan data dari kedua lembaga pemberantasan korupsi negara tersebut. Hasil penelitian menunjukkan bahwa terdapat tiga pilar kunci dalam pemberantasan korupsi di Singapura yang terdiri dari political will, independesi dan efektivitas lembaga pemberantasan korupsi, dan penerapan pelayanan administrasi yang baik. Hasil penelitian berikutnya memaparkan bahwa pemberantasan korupsi pada kurun 2015-2019 di Indonesia dirasa tidak optimal karena tiga hal: patronisme politik dan kuasa pemodal yang menghambat pemberantasan korupsi, ketidakefektifan penindakan KPK, dan visi kepemimpinan Jokowi yang terlalu fokus pada pembangunan dan pertumbuhan ekonomi namun kurang memperhatikan agenda pembaharuan birokrasi. Manfaat penulisan ini terutama ditujukan untuk membantu Indonesia dalam optimalisasi pemberantasan korupsi dengan belajar dari Singapura. Harapannya kepemerintahan yang baik dan bebas korupsi dapat terselenggara di Indonesia.